Characterization of cDNAs encoding human leukosialin and localization of the leukosialin gene to chromosome 16. - Pallant, A (1989)
We describe the isolation and characterization of cDNA clones encoding human leukosialin, a major sialoglycoprotein of human leukocytes. Leukosialin is very closely related or identical to the sialophorin molecule, which is involved in T-cell proliferation and whose expression is altered in Wiskott-Aldrich syndrome (WAS), an X chromosome-linked immunodeficiency disease. Using a rabbit anti-serum to leukosialin, a cDNA clone was isolated from a lambda gt11 cDNA library constructed from human peripheral blood cells. This lambda gt11 clone was used to isolate longer cDNA clones that correspond to the entire coding sequence of leukosialin. DNA sequence analysis reveals three domains in the predicted mature protein. The extracellular domain is enriched for Ser, Thr, and Pro and contains four contiguous 18-amino acid repeats. The transmembrane and intracellular domains of the human leukosialin molecule are highly homologous to the rat W3/13 molecule. RNA gel blot analysis reveals two polyadenylylated species of 2.3 and 8 kilobases. Southern blot analysis suggests that human leukosialin is a single-copy gene. Analysis of monochromosomal cell hybrids indicates that the leukosialin gene is not X chromosome linked and in situ hybridization shows leukosialin is located on chromosome 16. These findings demonstrate that the primary mutation in WAS is not a defect in the structural gene for leukosialin.